2014
DOI: 10.4269/ajtmh.14-0144
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Hepatitis E Virus Circulation in Domestic Pigs in Nigeria

Abstract: Abstract. Hepatitis E virus (HEV) is an important cause of acute hepatitis in humans. Zoonotic transmission between pigs and humans has been confirmed. Human HEV infection is common in Nigeria; however, characterization of HEV infection in other species was lacking. The objective of this study was to investigate HEV infection in Nigerian pigs. A total of 286 serum samples from six states in Nigeria were tested for presence of anti-HEV IgG. Ninety fecal samples from one of these states (Plateau State) were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 23 publications
4
24
4
Order By: Relevance
“…We noted high anti-HEV seropositivity in this study of 47.7% similarly to the 43.2% that was previously reported in the North and West regions of Cameroon [12], confirming that pigs are indeed a main reservoir for HEV. We noted anti-HEV IgM and IgG seropositivity of 21.0% and 17.7% respectively which is higher than reports from Nigeria and Mexico and lower than reports from Madagascar and Scotland [2,10,14,15]. These differences could be explained, at least partly, by the different pig husbandry systems, the routine management and hygiene practices applied on these pig farms and environmental conditions that characterize various areas [16].…”
Section: Discussioncontrasting
confidence: 61%
“…We noted high anti-HEV seropositivity in this study of 47.7% similarly to the 43.2% that was previously reported in the North and West regions of Cameroon [12], confirming that pigs are indeed a main reservoir for HEV. We noted anti-HEV IgM and IgG seropositivity of 21.0% and 17.7% respectively which is higher than reports from Nigeria and Mexico and lower than reports from Madagascar and Scotland [2,10,14,15]. These differences could be explained, at least partly, by the different pig husbandry systems, the routine management and hygiene practices applied on these pig farms and environmental conditions that characterize various areas [16].…”
Section: Discussioncontrasting
confidence: 61%
“…The HEV sequence, identified in this Burkinabe pig, was clustered with an African sequence of genotype 3 HEV from Yaounde (Cameroun) and Madagascar and had a > 98% similarity but was very different from the Nigerian strains as shown by BLAST analysis. 15 The phylogenetic analysis of the swine HEV-Burkina sequence, together with retrieved sequences and reference sequences, showed that the Burkinabe sequence is related to swine HEV strains from Cameroun and Madagascar but not from Congo (bootstrap value = 85; Figure 2). Addition of other published swine HEV sequences showed that our strain is part of a group of sequence with no subtype or geographical origin cluster (Supplemental Figure 1).…”
Section: -14mentioning
confidence: 98%
“…HEV1 and HEV2 infect only humans, while HEV3 and HEV4 also infect several mammalian species such as domestic pigs, wild boar, rabbit, deer, rat, and mongoose [ 4 ]. HEV3 strains infecting swine, rabbits, and humans have been described from the Americas, Europe, Asia, Oceania, and recently Africa [ 5 , 6 , 7 ]. Strains belonging to HEV4 have mainly been found in Asia, but recently also in Europe [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%